2017
DOI: 10.1007/s11606-017-4062-6
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in US Healthcare Provider Screening and Advice for Cessation Across Chronic Medical Conditions and Tobacco Products

Abstract: Results support the need for provider training to expand screening and cessation interventions to include the growing spectrum of tobacco products. Screening and referral to interventions are especially needed for those with mental health and substance use disorders to reduce the disparate burden of tobacco-related disease and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 30 publications
6
31
0
Order By: Relevance
“…Our findings are also consistent with earlier reports that 60 percent of patients in CHCs in New York City were missing smoking documentation between 2009 and 2012, and that 85 percent of patients in a nationally representative sample reported that providers asked them about tobacco use in 2013‐2014 . Like our study, both of these studies found that smoking documentation was significantly more common for patients with comorbidities than for those without.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are also consistent with earlier reports that 60 percent of patients in CHCs in New York City were missing smoking documentation between 2009 and 2012, and that 85 percent of patients in a nationally representative sample reported that providers asked them about tobacco use in 2013‐2014 . Like our study, both of these studies found that smoking documentation was significantly more common for patients with comorbidities than for those without.…”
Section: Discussionsupporting
confidence: 92%
“…32 This study is the first to examine rates of smoking documenta- about tobacco use in 2013-2014. 35 Like our study, both of these studies found that smoking documentation was significantly more common for patients with comorbidities than for those without. Additionally, both our study and the New York study found that smoking status documentation was more common for older patients.…”
Section: Discussionsupporting
confidence: 71%
“…Several recent studies have examined cigarette smoking and other tobacco use among those with and without chronic health conditions. Individuals with chronic conditions have higher prevalence of smoking and non-cigarette tobacco use, and have not exhibited the same declines in smoking prevalence over time as those without chronic conditions ( Keith et al, 2017 ; Stanton et al, 2016 ). However, there is promising evidence to suggest that individuals with chronic health conditions attempt to quit smoking at higher rates than those without these conditions and may also have greater motivation to quit ( Duffy et al, 2011 ; Gaalema et al, 2018 ; Kalkhoran et al, 2018 ).…”
Section: Introductionmentioning
confidence: 97%
“…Such advice is especially needed by African-American smokers because they have lower smoking quit rates than Whites, and suffer disproportionately from tobacco-related diseases ( Trinidad et al, 2011 ; Haiman et al, 2006 ). Studies have found however that African-American smokers are significantly less likely than White smokers to receive cessation advice from HCPs ( Danesh et al, 2014 ; Kruger et al, 2012 ; Lopez-Qunitero et al, 2006 ; Reed and Bums, 2008 ; Houston et al, 2005 ; Cokkinides et al, 2008 ; Keith et al, 2017 ). Demographic (i.e., age, gender), healthcare (i.e., health insurance, a regular doctor), amount of smoking, and health status (i.e., hypertension, diabetes, obesity) contribute to receiving cessation advice from HCPs, but racial disparities in receipt of that advice remain after controlling for those variables ( Danesh et al, 2014 ; Kruger et al, 2012 ; Lopez-Qunitero et al, 2006 ; Reed and Bums, 2008 ; Houston et al, 2005 ; Cokkinides et al, 2008 ; Keith et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%